Irrigation scheduling for green beans grown in clay loam soil under a drip irrigation system - Mohamed E Abuarab; Salma M Hafez; Mohamed M Shahein; Ahmed M Hassan; Mohamed BI El-Sawy; Mohamed M El-Mogy; Emad A Abdeldaym (Water SA, 2020)
An experimental field trial was conducted at El-Ayat, El-Giza Governorate, Egypt (latitude 30°11´13"N, longitude 31°41´38"E, and mean altitude 74 m above sea level) during the growing season of 2017 and 2018. The study aimed to assess the suitable irrigation interval and applied water volume for drip-irrigated green beans, based on water production functions and water use–yield relationships. The field trial was arranged in a split-plot design with 3 irrigation intervals (F1, F2 and F3 irrigation events, once every 1, 2 and 3 days, respectively) and 3 irrigation regimes (I1: 1.00, I2: 0.80, and I3: 0.60 of the crop evapotranspiration, ETc). The results showed that the yield and water use efficiency (WUE) increased with increasing irrigation interval. Maximum and minimum yield of 12 030 and 4 879 kg∙ha-1 were obtained in F1I2 and F3I3 treatment, respectively, in the winter season of 2017, and were 12 364 and 4 678 kg∙ha-1 for the corresponding treatments in the winter season of 2018. WUE ranged from 56.55 kg∙ha-1∙mm-1 in F1I2 to 23.80 kg∙ha-1∙mm-1 in F3I3. Plant growth parameters were significantly affected by the irrigation schedule. The highest plant growth parameters were obtained under F1 and F2. The seasonal yield response factors (ky) were 0.845 and 0.856 in 2017 and 2018, respectively. The relationship between yield and seasonal crop ET was best explained by a power function for all irrigation schedules for both growing seasons. It is recommended that the F1I2 irrigation treatment is the suitable one for green beans grown under field conditions, in order to achieve the highest yield and WUE.